Cosmology and Self in the Apostle Paul The Material Sprit - Engberg-Pedersen, Troels (Oxford OUP Oxford, 2010)
Cosmology and Self in the Apostle Paul challenges the traditional reading of Paul. Troels Engberg-Pedersen argues that the usual, mainly cognitive and metaphorical, ways of understanding central Pauline concepts, such as 'being in Christ', 'having God's
Keywords: Bible. -- Epistles of Paul -- Criticism, interpretation, etc. Bible. -- Epistles of Paul. Biblical cosmology